EQUIPMENT NOWADAYS (European Journal of Emerging Technology and Discoveries, 2023)
Today, the development of technology and the types of new technologies are being developed a lot. This technology includes Digital Cameras, Laptops, Pocket Computers, and many other techniques, these technologies are in demand. Digital cameras NIKON The design of this camera leaves a good effect on a person. It can be collected in a small and thin state (108x73x69 ml) as well as in a frog pocket